Intracranial Brain Volume (ICV) Measurement in Epileptic Male Patient: A 3D CT Study - Shirin, Lubna; Noor, Nor Farid Mohammed; Begum, Tahamina; Samsudin, Hadif Zaidin; Basri, Rehana; Abdullah, Johari Yap; Kabir, Mohammed Shahjahan; Alam, Mohammad Khursheed (Journal of Medicine, 2021)
Objective: Intracranial volume (ICV) is one of the reliable indicators of neurodegenerative disease and premature brain size. Epilepsy is considered a neurological disorder. We aimed to measure ICV in epileptic male samples to identify the relation of ICV and epilepsy control status for their better treatment purpose. Methods: This retrospective study was done using CT images of age-matched control and epileptic male samples. All samples were collected from the archive of the Department of Radiology, Universiti Sains Malaysia (USM) from the 2010-2017 period. A total of 34 male samples were used for this study in two groups, control (n=17) and epileptic (n=17) groups. Control males were those who came for the CT scan and no disease was found. And epileptic male patients were those who came for routine checkups due to epilepsy. MITK 3M3 software was used for the ICV measurement. 2D CT images were converted to 3D CT images to measure intracranial brain volume (ICV) in each group. Two reviewers measured ICV and a reliability test was done between reviewers. Results: According to first reviewer, there is no significant (p=0.455) difference between control, (1287.82 (151.79) mm) and epileptic (1283.28 (65.48) mm) male groups. Results of second reviewer also showed no significant difference (p=0.400) between control (1299.58(144.81)) mm and epileptic (1283.88 (76.08)) groups. Average measurements also did not reveal any significant difference between groups, control is 1293.7 (144.81) mm and the epilepsy group is 1283.58 (69.90) mm (p=0.114). Reliability test results revealed an acceptable internal consistency level in control (97%, p<0.001) and epileptic (77%, p=0.003) groups. Conclusion: We concluded that epilepsy does not affect ICV in the male population. Further study is recommended to seek other indicators which might be affected by epilepsy in the male population. J MEDICINE 2021; 22: 95-99